Определенные высотно-временного распределения электронной концентрации в диапазоне высот 100-1000 км - Черняк, Ю. В. (НТУ "ХПИ", 2004)
The method of measurement N, what based on the use of sounding signal compound, is developed. The additional channel metering with the improved height resolution is implemented. The information concerning distribution N in the regions of the E and F ionosphere is obtained during equinox
Keywords: ионосфера; ионосферная плазма; метод некогерентного рассеяния; радиоимпульсы; диапазон высот; зондирующий сигнал